The Potential Of Army Worm Spodoptera frugiperda J.E. Smith, Control On Corn Plant Using Sex Pheromones - Juliet Merry Eva Mamahit; Sandra Pakasi; Joice Rompas; Frangky J. Paat (Jurnal Agroekoteknologi Terapan, 2022)
The fall armyworm Spodoptera frugiperda J. E. Smith is an invasive pest of maize in Indonesia. The fall armyworm is a polyphagous pest originating from North America which was first discovered in West Africa. This pest control is very difficult because farmers are generally focused on the use of pesticides. For this reason, the method of using sex pheromones is an environmentally friendly alternative for controlling fall armyworm S. frugiperda pests. Innovation in the use of sex pheromones to act as attractants, mating disruption and mass trapping for controlling S. frugiperda pests. Keywords: pheromone, fall armyworm, Spodoptera frugiperda, corn Abstrak Ulat grayak tanaman jagung Spodoptera frugiperda J. E. Smith merupakan hama infasif di Indonesia. Hama ulat grayak, merupakan hama polifag yang berasal dari Amerika Utara yang pertama kali ditemukan di Afrika Barat. Pengendalian hama ini sangat sulit karena petani umumnya terfokus pada penggunaan pestisida. Untuk itu metode pemanfaatan feromon sex merupakan alternatif untuk pengendalian hama S. frugiperda yang ramah lingkungan. Inovasi pemanfatan feromon sex berperan sebagai atraktan, mengganggu terjadinya kopulasi antara jantan dan betina dan perangkap masal untuk pengendalian hama S. frugiperda. Kata kunci : feromon, ulat grayak, Spodoptera frugiperda, jagung